EFFECT OF SALINITY ON THE SURVIVAL, GROWTH AND IMMUNITY RATE OF JUVENILE SEA CUCUMBERS (Holothuria scabra) - Sari Budi Moria Sembiring; Gigih Setia Wibawa; Jhon Harianto Hutapea; I Nyoman Adiasmara Giri (BIOTROPIA, 2019)
Sea cucumber (Holothuria scabra) is an important species as food and medicine, especially for the Chinese market. It is a stenohaline and osmoconforming organism with a low level of tolerance to salinity change. Salinity of the medium is one of the environmental factors that affect the physiology and survival of juvenile sea cucumbers. This study was aimed at assessing the effect of different salinities on the growth, survival and immunity rate of juvenile sea cucumbers (Holothuria scabra) and also determining the suitable salinity level for the optimal growth, survival and immunity rate of the sea cucumbers. This experiment used a completely randomized design with 5 salinity treatments: 24, 29, 34, 39, and 44 ppt with 3 replications using fifteen 30 L fiberglass tanks. The juvenile sea cucumbers measured 4.4 ± 0.2 cm in total length and 5.6 ± 0.3 g in body weight. The juveniles were raised at 15 individuals/tank, fed with cultured fresh benthos once a day in the afternoon. Coelomate was taken from the sea cucumber juveniles from each tank and used to determine the immunity rate and also for the osmolality. The data were analyzed using ANOVA followed by Tukey's test at 5% level of significance. The salinity of the medium significantly affected (p < 0.05) the growth, survival rate and immunity rate of sea cucumber juveniles. The 24–34 ppt salinity can support survival rate up to 100%, high growth (6.47–7.10 g) and immunity rate (27–76 × 10⁴ phagocytic cells/mL), while the 44 ppt salinity has resulted in not only a low survival rate (55.60%), but also had a bad effect on osmolality (303 ± 3.5 mOsm/kg), growth (3.12 ± 0.34 g), and immunity (209 × 10⁴ phagocytic cells/mL).